‘An invisible human rights crisis’: The marginalization of older adults during the COVID-19 pandemic – An advocacy review - D'cruz, Migita; Banerjee, Debanjan (Psychiatry research, 2020)
•Coronavirus disease 2019 (COVID-19) has emerged as a global health threat.•Older adults form a vulnerable section both to the physiological risks of infection as well as to the psychosocial offshoots of distancing and lockdown.•Loneliness, isolation, abuse, loss of autonomy, and restriction of health care access can accentuate their frailty and comorbidities.•The authors propose marginalization as the probable common pathway for human rights deprivation of older adults during the pandemic.•Measures of mitigating these effects enabling Healthy Aging are discussed. The world has endured over six months of the Coronavirus disease 2019 (COVID-19). Older adults are at disproportionate risk of severe infection and mortality. They are also vulnerable to loneliness and social exclusion during the pandemic. Age and ageism both can act as significant risk factors during this pandemic, increasing the physical as well as psychosocial burden on the elderly. A review was performed in relation to the psychosocial vulnerabilities of the older adults during the pandemic, with insights from the similar biological disasters in the past. Besides the physiological risk, morbidities, polypharmacy and increased case fatality rates, various social factors like lack of security, loneliness, isolation, ageism, sexism, dependency, stigma, abuse and restriction to health care access were identified as crucial in pandemic situation. Frailty, cognitive and sensory impairments added to the burden. Marginalization and human rights deprivation emerged as a common pathway of suffering for the elderly during COVID-19. The implications of the emergent themes are discussed in light of psychosocial wellbeing and impact on the quality of life. The authors suggest potential recommendations to mitigate this marginalization on lines of the World Health Organization (WHO)’s concept of Healthy Ageing and the United Nations (U.N.) Sustainable Development Goals.